2021
DOI: 10.5194/acp-21-9417-2021
|View full text |Cite
|
Sign up to set email alerts
|

Rapid transformation of ambient absorbing aerosols from West African biomass burning

Abstract: Abstract. Seasonal biomass burning (BB) over West Africa is a globally significant source of carbonaceous particles in the atmosphere, which have important climate impacts but are poorly constrained. Here, the evolution of smoke aerosols emitted from flaming-controlled burning of agricultural waste and wooded savannah in the Senegal region was characterized over a timescale of half-day advection from the source during the MOYA-2017 (Methane Observation Yearly Assessment-2017) aircraft campaign. Plumes from suc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 107 publications
1
18
0
Order By: Relevance
“…For relatively fresh smoke, Palm et al (2020) conclude that a balance between dilution-driven evaporation of primary wildfire smoke chromophores and formation of secondary BrC led to the observation in nine fire plumes of a near-constant level of light absorption by BrC for smoke up to at least 6 hours old. Wu et al (2021) found that smoke from West-African prescribed fires that started with minor levels of BrC, but were rich in BC, had continual increases in BrC with plume age for up to 12 hours. Studies tracking smoke over longer time scales have shown an overall loss of BrC, with a BrC characteristic lifetime (e.g., e-folding lifetime) ranging from ~10 hours to days (Forrister et al, 2015;Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For relatively fresh smoke, Palm et al (2020) conclude that a balance between dilution-driven evaporation of primary wildfire smoke chromophores and formation of secondary BrC led to the observation in nine fire plumes of a near-constant level of light absorption by BrC for smoke up to at least 6 hours old. Wu et al (2021) found that smoke from West-African prescribed fires that started with minor levels of BrC, but were rich in BC, had continual increases in BrC with plume age for up to 12 hours. Studies tracking smoke over longer time scales have shown an overall loss of BrC, with a BrC characteristic lifetime (e.g., e-folding lifetime) ranging from ~10 hours to days (Forrister et al, 2015;Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The stratospheric aerosol layer contributes ∼ 0.005 to ∼ 0.01 to mid-visible AOD measured by AERONET (e.g., Yang, 2017) but not to that derived from the DC-8 profiles. The contribution of stratospheric AOD was determined using the Global Space-based Stratospheric Aerosol Climatology (GLOSSAC) v. 2.0 (NASA/LARC/SD/ASDC, 2018; Kovilakam et al, 2020).…”
Section: Aod and Comparison With Aeronetmentioning
confidence: 89%
“…Airborne measurements of CH 4 were recorded over Zambia in February 2019 as part of the Methane Observations and Yearly Assessments (MOYA; Barker et al, 2020;Wu et al, 2021) ZWAMPS field campaign. Three wetland areas were targeted across three separate flights; the Bangweulu wetland region in north-eastern Zambia (11°36' S, 30°05' E), the Kafue wetland in southern Zambia (15°43' S, 27°17' E), and the Lukanga wetland in central Zambia (14°29' S, 27°47' E) (Figure 1).…”
Section: Methodsmentioning
confidence: 99%